Gambaran Kualitas Hidup ODHA yang Menjalani Terapi Antiretroviral (ARV) di Poli Cendana RSUD Ngudi Waluyo Wlingi - Erni Setiyorini (Journal of Ners and Midwifery, 2015)
Human Immunodeficiency Virus (HIV)is desease with high mortality and everyone have chance got HIV. At Blitar HIV/AIDS prevalence increase since 2010. The incubation of HIV need long time to become AIDS. At this period PLWHA faced with physic, physichologic, sosial, environment problem and impact to their quality of life. The purpose of this study was to describe quality of life PLWHA at physic, physichologic, sosial, environment dimension. Method: Research design was descriptive. Population of this study is PLWHA who receiving ARV at Cendana Clinic Ngudi Waluyo Wlingi Hospital. Samples 42 respondent by using convenient sampling. Data collected at September 1st– 30, 2013 by questionaire. Result of this study in physic dimension much of them at good 16 peoples (38,1%), enough and less, each of them 13 peoples (31%). Physhicology dimension at good and enough, each of them 20 peoples (47,6%) then at less 2 peoples (4,8%). Sosial dimension enough 25 peoples (59,5%), good 15 peoples (35,7%) and less 2 peoples (4,8%). Environment dimension enough 16 peoples (38,1%), good 15 peoples (35,7%) dan kurang 11 orang (26,2%). It is suggested for nurse to implementation nursing care plan to PLWHA suitable with their quality of life dimension and enhance support to their sosial activity.